Evaluasi Social Media Marketing Pada Instagram Dalam Upaya Meningkatkan Volume Penjualan Produk - Silfi Muna’am Maulidiyyah, Neng; Azhar Solihin, Shofwan; Sudewa, Jaka (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Social Media Marketing (SMM) is a marketing strategy that uses social media platforms to achieve business goals, including increasing brand awareness, building relationships with customers, and of course increasing sales volume. The purpose of this research is to find out what efforts Ziebarmart needs to make in order to optimize the implementation of Social Media Marketing on Ziebarmart's Instagram. This research uses a quantitative descriptive approach which aims to evaluate the application of Social Media Marketing on Instagram in an effort to increase sales volume using purposive sampling data collection techniques. Data processing was obtained from interviews, questionnaires, observations and literature studies. The research results show an average expectation (Ȳ) of 3.24 and an average implementation (X̄) of 2.40, which is included in the main priority quadrant, namely indicators of current content (7), Consistent (8), Service adjustments (10 ). So the things that cooperatives need to do to increase Ziebarmart's sales volume include creating up-to-date content, improving the consistency of content uploads, adjusting services, improving interactions, and increasing Word of Mouth.